Developing English – Indonesia Pictorial Vocabulary Mini Dictionary for Hearing Impaired Students - Putera, Alam Aji; Paraswati, Hazlinda; Kamila, Elva Laela; Putri Nabila, Diva Amilta (Journal Of Foreign Language Learning and Teaching, 2023)
This research aims to develop an Indonesian English dictionary for hearing-impaired students at Special School of Linguistics (SLB) Idayu Malang 2. The research titled "Developing English - Indonesia Pictorial Vocabulary Mini Dictionary for Hearing Impaired Students" aimed to create a comprehensive and accessible vocabulary resource for students with hearing impairments. This study aspires to contribute to the broader objective of fostering inclusivity in language education by introducing an innovative and accessible tool that promotes vocabulary acquisition. Through a systematic data collection and analysis process, the research aimed not only to understand existing challenges but also provide a tailored solution through the development of an inclusive Thematic Dictionary Application. The data that has been collected is then used as a basis for researchers to develop a good English-Indonesia Dictionary for hearing impaired learning media design so that it can be used to deal with problems that occur in hearing impaired students in SLB. Based on these findings, it is concluded that the English module for EYL hearing-maternal language (EYL) hearing impaired children can be use with slight revisions.